SEROLOGICAL STUDY OF BOVINE LEUKOSIS IN IRAQ LOCAL BREED AND IMPORTED COW - Yousif , Afaf Abd - Al-Rahmain (The Iraqi Journal of Veterinary Medicine, 2022)
Two hundreds and sixteen blood samples from Iraqi local breed cows in Baghdad, Basrah, Diala provinces and 144 blood samples from imported cows in three large cows stations were collected. All samples were tested by ELISA for the detection of specific antibody to bovine leucosis. Results revealed the presence of antibodies of 8.4 % in imported cows only. Whereas the blood samples from the local animals included in this study were negative.